2002
DOI: 10.1038/sj.bjc.6600569
|View full text |Cite
|
Sign up to set email alerts
|

Role of biological markers in the clinical outcome of colon cancer

Abstract: We investigated a number of biological markers, evaluated under strict intralaboratory quality control conditions, in terms of their role in predicting clinical outcome of patients with colon cancer treated with 5-FU-containing regimens. Colon cancer tissue from 263 patients enrolled onto two randomised clinical trials were studied for their cytofluorimetrically determined DNA content and their immunohistochemically evaluated microvessel density, vascular endothelial growth factor expression, thymidylate synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1
1

Year Published

2006
2006
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 53 publications
(54 reference statements)
2
34
1
1
Order By: Relevance
“…Moreover, the lack of a prognostic association for endothelial Dll4, a VEGF target (Patel et al, 2005), is in agreement with the lack of a prognostic association for VEGF in colon cancer in this study and elsewhere (Nanni et al, 2002;Zheng et al, 2003;Jubb et al, 2006a). In this study the expression of CA9 was not prognostic in terms of overall survival, in contrast to a report that expression of CA9 is a poor prognostic factor in colorectal cancer (Cleven et al, 2007).…”
Section: Spatial Regulation Of An Appropriate Level Of Dll4 Expressiocontrasting
confidence: 56%
“…Moreover, the lack of a prognostic association for endothelial Dll4, a VEGF target (Patel et al, 2005), is in agreement with the lack of a prognostic association for VEGF in colon cancer in this study and elsewhere (Nanni et al, 2002;Zheng et al, 2003;Jubb et al, 2006a). In this study the expression of CA9 was not prognostic in terms of overall survival, in contrast to a report that expression of CA9 is a poor prognostic factor in colorectal cancer (Cleven et al, 2007).…”
Section: Spatial Regulation Of An Appropriate Level Of Dll4 Expressiocontrasting
confidence: 56%
“…Thirty-two independent studies representing 3496 patients with mean age of 64.7 years (1740 male patients, 1400 female patients) included 1449 colon and 673 rectum cancers. These studies included 286 stage A, 1315 stage B, 1085 stage C and 388 stage D. There were only eight series of consecutive patients (Lindmark et al, 1996;Ishikawa et al, 1999;Vermeulen et al, 1999;Pietra et al, 2000;Prall et al, 2003;Shan et al, 2003;Galizia et al, 2004;Liang et al, 2004) and one prospective study (Nanni et al, 2002), compared to 23 retrospective studies.…”
Section: Resultsmentioning
confidence: 99%
“…The main features of eligible studies for VEGF are summarized in Table 2 Takahashi et al, 1997;Cascinu et al, 2000;Maeda et al, 2000;Cascinu et al, 2001;Cascinu et al, 2002;Nanni et al, 2002;White et al, 2002;Galizia et al, 2004) for RFS and 10 for OS (n ¼ 1301) (Ishigami et al, 1998;Tokunaga et al, 1998;Lee et al, 2000;Harada et al, 2001;Nanni et al, 2002;White et al, 2002;Kaio et al, 2003b;Khorana et al, 2003;Zheng et al, 2003;Tamura et al, 2004). High VEGF significantly predicted poor RFS (RR ¼ 2.84; 95% CI: 1.95 -4.16; Po0.001) and poor OS (RR ¼ 1.65; 95% CI: 1.27 -2.14; Po0.001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has already been demonstrated that neovascularization is associated with tumor growth and that the possibility exists that tumors with greater numbers of microvessels are related to metastases 16,17,18 . In fact, a relationship between the degree of microvessel density and worse prognosis for colorectal cancer has been observed in several studies 4,5,19 , although this has not been confirmed by some other authors 20,21,22 . These differences in results have been attributed in part to limitations in the traditional method for assessing angiogenesis 7,8,23 .…”
Section: Discussionmentioning
confidence: 81%